ON POSSIBILITY OF MODELING OF INFLUENCE OF ANTIPENETRATION WASH ON HEATING PROCESSES IN THE PERIOD OF MOLD FILLING WITH MELT - D. M. Kukuj; Ju. A. Nikolajchik; L. V. Sudnik (Литьë и металлургия, 2009)
It is shown that the received results of investigations allow to state possibility of modeling of heat processes with the help of system «Polygosoft».